Effect of the structure of polarimeter characteristic matrix on light polarization measurements - Savenkov, S.N.; Oberemok, Ye.A.; Klimov, O.S.; Barchuk, О.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
In the paper, we carried out the comparative analysis of three polarimeters among the most usable their variants: (i) Stokes polarimeter based on phenomenological definition of Stokes parameters; (ii) Stokes polarimeter based on the method of four intensities; (iii) Stokes dynamic polarimeter. We show that, since the accuracy in determination of individual Stokes parameter is different for different types of polarimeters, and, therewith, it depends on polarization of input light. All that strongly motivates the choice of type of polarimeter to provide minimum errors in determination of polarization parameters (ellipticity angle ε, azimuth β, and degree of polarization P).